Моделі емпіричного навчання дорослих: зарубіжний досвід - Майя Дернова (Pavlo Tychyna Uman State Pedagogical University, 2015)
У статті проаналізовано моделі емпіричного навчання, які існують у зарубіжній теорії і практиці освіти дорослих. Серед них моделі Д. Колба, Л. Джоплін, Д. Бауда і Д. Уокера, Г. Діна, Дж. Пфайффер і Дж. Джонс та К. Ітіна. Визначено, що в їх основі лежить трансформація й інтерпретація досвіду самих студентів; викладач відіграє роль фасилітатора або тренера, а не перекладача реальності або постачальника істини; озброюють студентів компетенціями, яких вони потребують для успіху у реальному світі й створюють унікальну можливість для підготовки студентів до професійної кар'єри. В статье проанализированы модели эмпирического обучения, которые существуют в зарубежной теории и практике образования взрослых. Среди них модели Д. Колба, Л. Джоплин, Д. Бауда и Д. Уокера, Г. Дина, Дж. Пфайффер и Дж. Джонс, а также, К. Итина. Определено, что в их основе лежит трансформация и интерпретация опыта самих студентов; преподаватель играет роль фасилитатора или тренера, а не переводчика реальности или поставщика истины; вооружают студентов компетенциями, в которых они нуждаются для успеха в реальном мире и создают уникальную возможность для подготовки студентов к профессиональной карьере. This article analyzes the models of adults experiential learning which exist in foreign theory and practice of adult education. Among them are D. Kolb's, L. Joplin's, D. Baud's and D. Walker's, G. Dean's, J. Pfeiffer's and J. Jones's as well as K. Itin's models. Experiential learning theory defines learning as the process of knowledge creation through the transformation of experience, so knowledge is the result of experience understanding and transformation. Experience understanding is the process of taking information, and experience transformation is an interpretation of information and action based on this information. As a process, experiential learning is cyclical in nature and requires an initial focus of the learner, followed by interaction with the phenomenon being studied, reflecting on the experience, developing generalizations, and then testing those generalizations. In the centre of experiential learning models is a learning process, but subject matter is also important. So educators characterize experiential learning in two ways. The first set of theories focuses on the process of experiential learning; the second set of theories relates to the context in which experiential learning takes place. The experiential learning is designed to engage students in direct experiences which are tied to real world problems and situations in which the instructor facilitates rather than directs student progress. Experiential learning motivates students and creates self-directed life-long learners. It has been concluded that models of adults experiential learning are based on the transformation and interpretation of students' experience; teacher acts as a facilitator or coach, not the interpreter of truth provider; equip students with competencies they need for success in the real world and give students a unique opportunity to prepare them for professional careers.